Implementation of Facilities and Infrastructure at Pesantren Pelajar Mahasiswa Aswaja Nusantara: Opportunities and Challenges - Putri, Zifa Ayu; Fadhilah, Lailaturrohmah (Proceeding International Conference on Religion, Science and Education, 2025)
The condition of educational facilities and infrastructure in pesantren is built simply, which only prioritizes the process of continuing learning activities and direct interaction between students and teachers, but there is no adequate support for utilization and organization. Facilities and infrastructure are one of the important things to always pay attention to in educational institutions. Well-managed facilities and infrastructure in an educational institution are influential in supporting the learning process. This study aims to analyze the implementation of facilities and infrastructure management at the Pesantren Pelajar Mahasiswa Aswaja Nusantara and identify opportunities and challenges faced in its management. The research was conducted using a descriptive qualitative approach, collecting data through field observations, interviews, and documentation. Then, data analysis was carried out by reducing data, presenting data, and drawing conclusions. The results showed that Pesantren Pelajar Mahasiswa Aswaja Nusantara has implemented facilities and infrastructure management by planning, procurement, maintenance, deletion, and control and evaluation. The pesantren has also succeeded in utilizing digital technology as a means and infrastructure to support learning activities. However, the challenges faced are the limited ownership of pesantren buildings, less than optimal maintenance of facilities, and the lack of equal distribution of infrastructure facilities between the central dormitory and branch dormitories. In conclusion, although there are significant challenges in managing facilities and infrastructure, this pesantren is able to take advantage of existing opportunities by working with the Ministry of Youth and Sports to be able to develop pesantren facilities and infrastructure. The pesantren education institution should increase efforts to maintain facilities and pay attention to more effective organization to overcome the challenges of building limitations and equal distribution of facilities between the central and branch dormitories. These steps are expected to better support success in the learning process.